Pengaruh Kecemasan Matematika terhadap Hasil Belajar Siswa SMA Kelas X - Nadya Wardani (NUCLEUS, 2022)
This research purpose is to acknowledge anxiety level of math, student study results, and how far is the effect of math anxiety to student study results. The research method that used was ex post facto with sample that being used was X grade student. The instrument that used in this research is questionnaire of math anxiety and score table of student study results. Based on the research analysis results, obtained result that the level of student anxiety was at high level, 2) the student study results was at low level, and 3) students anxiety gave negative effect to student study results.